2020
DOI: 10.2147/jhc.s285357
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Local Treatments for Hepatocellular Carcinoma Involving the Inferior Vena Cava and/or Right Atrium

Abstract: Major vessel invasion is frequently observed in locally advanced hepatocellular carcinoma (HCC). The most commonly involved major vessel is the portal vein; however, approximately 4% of patients with HCC have inferior vena cava (IVC) and/or right atrium (RA) invasion. Although these conditions have dismal prognoses, local treatments have not been regularly administered because they may affect systemic circulation. Owing to recent technological advances, various local treatments including surgery and external r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Patients typically have concomitant liver dysfunction, poor prognosis and high rate of recurrence; therefore, HCC with IVC invasion is considered an absolute contraindication to liver transplantation and managed non-surgically. However, recent studies have shown that sorafenib, external beam radiotherapy and surgery with careful patient selection can improve clinical outcomes [ 98 , 99 ].
Fig.
…”
Section: Secondary Malignancymentioning
confidence: 99%
“…Patients typically have concomitant liver dysfunction, poor prognosis and high rate of recurrence; therefore, HCC with IVC invasion is considered an absolute contraindication to liver transplantation and managed non-surgically. However, recent studies have shown that sorafenib, external beam radiotherapy and surgery with careful patient selection can improve clinical outcomes [ 98 , 99 ].
Fig.
…”
Section: Secondary Malignancymentioning
confidence: 99%
“…However, due to the risk of circulatory failure and the poor general status of patients with HCC RA TT, this approach is not compatible with all patients. Likewise, External beam radiation therapy is also not suitable for all patients due to the associated severe adverse effects and liver toxicity that may result from radiation doses exceeding 35 Gy [3,4,12].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional TACE is the most commonly used locoregional treatment for the management of HCC and is the recommended standard therapy for intermediate-stage HCC [12]. However, TACE is generally contraindicated for cases of HCC with IVC and RA TT due to the high number of associated complications which include: high-risk ischemic hepatic necrosis, pulmonary embolization, and metastasis [10].…”
Section: Discussionmentioning
confidence: 99%